Lived Experience of Treatment for Avoidant Personality Disorder: Searching for Courage to Be - Sørensen, Kristine Dahl; Wilberg, Theresa; Berthelsen, Eivind; Råbu, Marit (Frontiers in Psychology, 2019)
Objective: To inquire into the subjective experience of treatment by persons diagnosed with avoidant personality disorder. Methods: Persons with avoidant personality disorder (n = 15) were interviewed twice, using semi-structured in-depth interviews, and the responses subject to interpretative-phenomenological analysis. Persons with first-hand experience of avoidant personality disorder were included in the research process. Results: The super ordinate theme emerging from the interviews, “searching for courage to be” encompassed three main themes: “seeking trust, strength, and freedom,” “being managed,” and “discovering the possibility for change and development.” The main theme, “being managed,” included the subthemes: “getting a diagnosis,” “receiving medication,” and “attending therapy.” Conclusion: Although this may not be specific to avoidant personality disorder, the findings highlight the importance of being met inter-subjectively as a person with intentionality and agency, even when one does not feel like one. The importance of establishing an emotional bond and emergent trust for open therapeutic collaboration, learning, and becoming able to build courage to begin to approach that which one fears is emphasized.